2014
DOI: 10.1002/jbm.a.35353
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast response to the surface of amino acid‐functionalized hydroxyapatite

Abstract: Interactions between proteins and the surface of biomaterials are crucial for the biological function and success of materials implanted in the human body. In this study, hydroxyapatite (HA) with negative and positive surface charges were fabricated by functionalizing the HA surface with acidic or basic amino acids. The influence of HA surface charge on protein adsorption and cell activities was studied. The crystallinity, morphology, and surface charge of amino acid-functionalized HA (AA-HA) particles and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that bone tissue materials based on ceramics that lack sufficient inductivity, such as HA or beta calcium phosphate, do not efficiently promote bone formation (Culpepper et al , ). Many investigators have attempted to improve the bioactivity of scaffolds by incorporating bioactive molecules through chemical conjugation or physical absorption (Lee et al , ; Zhang et al , ). However, physical absorption exhibits passive release with an unsatisfactory release profile and short duration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that bone tissue materials based on ceramics that lack sufficient inductivity, such as HA or beta calcium phosphate, do not efficiently promote bone formation (Culpepper et al , ). Many investigators have attempted to improve the bioactivity of scaffolds by incorporating bioactive molecules through chemical conjugation or physical absorption (Lee et al , ; Zhang et al , ). However, physical absorption exhibits passive release with an unsatisfactory release profile and short duration.…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic strategies also involve functionalization of CaPs with organic molecules or macromolecules, as synthetic analogues of the acidic macromolecules present in biomineralized tissues, with the purpose of modulating CaP nucleation, growth, crystal structure, crystallinity and solu- bility. In particular, the interaction of CaPs with a variety of amino and polyamino acids has been investigated, to help clarify the mineralization process and to obtain materials able to provide an improved interfacial bonding with bone tissue (56)(57)(58)(59)(60).…”
Section: Functionalized Cap Crystalsmentioning
confidence: 99%
“…Amino acid is also an effective regulator of HAp nucleation and growth, and can signicantly affect the adsorption and release kinetics. [16][17][18][19] These cited studies found that an introduction of amino acids during synthesis of HAp changes the growth of initial crystalline domains along the c-axis and a-axis directions, thus changing morphology and dimensions of HAp particles.…”
Section: Introductionmentioning
confidence: 99%